LEPROSY IN THE POPULATION OVER 60 YEARS IN ALAGOAS: analysis of a historical series (Revista Brasileira Multidisciplinar, 2022)
Among the numerous pathologies that stimulate the functional decline of the elderly, leprosy is worth highlighting. An infectious, chronic and dermatoneurological disease, which compromises the peripheral nerves, and can worsen the functional difficulties assuming a disabling character, in addition to causing physical deformities when not properly treated. In this descriptive study with a quantitative approach, the objective was to analyze the data collected, in order to assess the epidemiological characteristics, clinical diagnosis and classification, through the occurrence of Hansen's disease in the elderly population in relation to other age groups in the state of Alagoas between the years of 2007 to 2020, based on data from the Notifiable Diseases Information System (SINAN). There was a prevalence of males making up 50.2% of the total population. The largest age group was 29-39, but there was a significant amount of the elderly population affected. As for the operational classification, there was a higher prevalence of the multibacillary form, comprising 798 cases. Regarding the degree of disability, males are more prevalent in cases of disability and physical impairment than females, with grade I affecting most male and female patients. Thus, it is concluded that care and treatment should be assertive and initiated as soon as possible, with a view to reducing, and the disabilities present in degrees of injuries, in the elderly population affected by the disease.
Keywords: leprosy. epidemioly. epidemiological surveillance.